2010
DOI: 10.1111/j.1574-6941.2010.00988.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estuarine sediment hypoxia on nitrogen fluxes and ammonia oxidizer gene transcription

Abstract: The effects of sediment hypoxia, resulting from increased carbon loads or decreased dissolved oxygen (DO), on nitrogen cycling in estuarine environments is poorly understood. The important role played by bacterial and archaeal ammonia oxidizers in the eventual removal of nitrogen from estuarine environments is likely to be strongly affected by hypoxic events. In this study, an analysis of the effects of different levels of sediment hypoxia (5%, 20% and 75% DO) was performed in a microcosm experiment. Changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…Our results thus suggest that (i) glycolipids are mainly derived from the water column, (ii) HPHcrenarchaeol is relatively rapidly degraded and (iii) benthic AOA are actively producing IPL-crenarchaeol in the (sub-)surface of the sediment underneath the OMZ, probably occupying a low oxygen niche (cf. Chen et al, 2008;Abell et al, 2011;. Interestingly, while the HPH-crenarchaeol shows subsurface maxima indicating in situ production, the ratio of IPL-derived vs. CL-crenarchaeol does not increase as perhaps would be expected (Fig.…”
Section: Sedimentary Production and Preservation Of Gdgtsmentioning
confidence: 65%
“…Our results thus suggest that (i) glycolipids are mainly derived from the water column, (ii) HPHcrenarchaeol is relatively rapidly degraded and (iii) benthic AOA are actively producing IPL-crenarchaeol in the (sub-)surface of the sediment underneath the OMZ, probably occupying a low oxygen niche (cf. Chen et al, 2008;Abell et al, 2011;. Interestingly, while the HPH-crenarchaeol shows subsurface maxima indicating in situ production, the ratio of IPL-derived vs. CL-crenarchaeol does not increase as perhaps would be expected (Fig.…”
Section: Sedimentary Production and Preservation Of Gdgtsmentioning
confidence: 65%
“…Previous studies have demonstrated that sediment, the primary site of estuarine nitrification, may contain both AOA and AOB, with some estuarine regions dominated by AOB (Mosier & Francis 2008, Santoro et al 2008) and others by AOA (Beman & Francis 2006, Abell et al 2010. The reason for the presence of one group of seemingly functionally equivalent groups over another in the environment is unclear, although it has been suggested that pH (Nicol et al 2008), nitrite (Sahan & Muyzer 2008), sulphide and phosphate (Erguder et al 2009) and salinity (Mosier & Francis 2008) may be important, whilst large variations in salinity, oxygen and hydrological factors may shape the structure of these communities (Stehr et al 1995, Cébron et al 2003, Francis et al 2003, Dang et al 2008, Abell et al 2010, Abell et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…NH 4 + concentration can also determine the differential growth of AOB and AOA in soil in that AOA prefers a less NH 4 + (Verhamme et al 2011). An increase in NH 4 + concentration is indicative of a reduced nitrification efficiency (Abell et al 2011). In treatment T3 in the present study, the NH 4 + concentration increased as that of NO 2 − increased after PNP degradation by strain WBC-3.…”
Section: Discussionmentioning
confidence: 42%
“…However, the magnitudes of the relative contributions of AOB and AOA, which have ecologically equivalent functions, to ammonia oxidation are still largely unknown. It has been suggested that many environmental factors including pH (Nicol et al 2008), salinity (Mosier and Francis 2008), NH 4 + (Hofferle et al 2010;Martens-Habbena et al 2009;Verhamme et al 2011), and dissolved oxygen concentration (Abell et al 2011) may play a critical role in their individual dominance and the niche segregation of ammonia oxidizers. These findings have stimulated a reassessment of ammonia-oxidizer community ecology, and consequently, the nitrification process in agricultural ecosystems should be re-evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation